Ameliorative Potential of Ursolic Acid Isolated from Morina coulteriana Royle Targeting P53 Gene Mutation Induced by Cyclophosphamide - kour, Jasbir; Lone, Bashir Ahmad; Shah, Naseer ue-din; Ganai, Bashir A.; Ali, Md. Niamat; Akbar, Seema (Asian Pacific Journal of Cancer Biology, 2024)
Objective: More than 50% of human cancers show mutated TP53 gene. Reactivation or restoration of p53 mutations is viewed as a potential approach for treating cancer. The objective of the present study was to determine whether ursolic acid (UA) could effectively restore the p53 mutations to their wild type or normal state and upregulate its expression. Methods: The animals were divided into 3 groups, each with 10 mice. Group I was the negative control which received normal saline with 1% dimethyl sulfoxide (DMSO). Group II was the positive control which received cyclophosphamide (CP) (50mg/kg bw) intrapritonealy for 4 days continuously after which the animals were kept on normal saline for the rest 10 days. The treatment group received cyclophosphamide (CP) initially for the first 4 successive days intraperitoneally (50mg/kg bw) and then ursolic acid (UA) (60 mg/kg bw) orally for the next 10 days (post-treatment). Isolated DNA was used in Sanger sequencing of the polymerase chain reaction (PCR) amplified product of the TP53 gene. Results: Our study demonstrated that UA treatment post CP injection had a restoration efficacy of 89.08%. The molecule, in this investigation, was able to restore the wild type (normal) conformation to the mutations induced by cyclophosphamide in the TP53 gene. 89.08 % mutations converted back to their normal or wild-type forms in the treatment group. Conclusion: Several investigations have been carried out on this molecule and have indicated UA as a promising chemopreventive agent. The most frequently mutated gene in any type of cancer is the tumor suppressor p53 and UA has shown a potential in functional restoration of the mutated p53 protein. p53 is known to play a vital role in apoptosis and the p53 dependent apoptotic pathway is of prime importance in cancer therapy. Though there has been pioneering work on PRIMA-1 and thiosemicarbazones, identification and development of additional molecules is required.